La Tentation de saint Antoine de Flaubert et Uspud d’Erik Satie : affinités secrètes et résonances en filigrane - Bruna Donatelli (Flaubert: Revue Critique et Génétique)
La Tentation de saint Antoine triggered almost exclusively the painters’ interest, until the 1880s: they were fascinated by its implicit iconic appeal and visionary universe. After the appearance of cabaret shows in Paris, however, the heterogeneous, scenic and textual space of this text was regarded differently and gained renewed vitality. Among the audacious artists who experimented new forms of hybrid art (magic shows, shadow plays, pantomimes, burlesque) in these cabarets, we count also Erik Satie, a great admirer of Flaubert and his works. In the wake of other adaptations of La Tentation de saint Antoine, performed in the Chat Noir and L’Auberge du Clou shadow theatres, Satie composed Uspud, ballet chrétien en trois actes, of which, together with Contamine de Latour, he also wrote the booklet. In this article, I highlight the similarities between Flaubert’s and Satie’s work: these similarities exceed, in fact, the textual parts of the latter’s booklet. I also focus on the elective affinity emerging through both authors’ approach and aesthetic taste.